Motivasi Memoderasi Pengaruh Pertimbangan Pasar Kerja, Lingkungan Kerja, Personalitas terhadap Minat Mahasiswa Menjadi Akuntan Publik - Suniantara, I Gede; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi; Vol 31 No 8 (2021), 2021)
The current phenomenon in Indonesia in the accounting sector is the lack of public accountants based on a statement from the Indonesian Institute of Certified Public Accountants (IAPI). The lack of interest in accounting students towards the public accounting profession is one of the results of the lack of accounting graduates becoming public accountants. Considerations of the labor market, work environment, personality and motivation are factors that influence student interest. This study will take a population, namely accounting students class 2017, Faculty of Economics, Udayana University. The samples obtained after using the Slovin method were 168 students. Moderated Regression Analysis (MRA) was used as the analysis technique for this study. The results of this study prove that considerations of the job market, work environment, personality and motivation affect the interest of accounting students to become public accountants. Keywords: Considerations Labor Market; Work Environment; Personality, Motivation; Interests.